2001
DOI: 10.1093/intimm/13.3.321
|View full text |Cite
|
Sign up to set email alerts
|

The non-classical MHC class I molecule Qa-1b inhibits classical MHC class I-restricted cytotoxicity of cytotoxic T lymphocytes

Abstract: The CD94/NKG2A heterodimer is an inhibitory receptor expressed on a subset of mouse NK cells. CD94/NKG2A recognizes the non-classical MHC class I (class Ib) molecule Qa-1(b) and inhibits NK cytotoxicity. Qa-1(b) presents a peptide derived from the leader sequence of classical MHC class I molecules. Here, we examined the role of CD94/NKG2A in T cell-mediated cytotoxicity. Soluble tetrameric Qa-1(b) bound to almost all CD8(+), but not CD4(+), T cells. This binding seems to be mediated by CD8, because COS cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
3
17
1
Order By: Relevance
“…A similar scenario may be applicable to the CD94/NKG2A expressed on donor T cells during aGVHD, which may represent an intrinsic mechanism that limits aGVHD pathology. Consistent with this notion, donor T cells expanded progressively in the spleen and liver during days 7-14 after transfer, but this expansion was rather suppressed during days [14][15][16][17][18][19][20][21] in the present aGVHD model (Fig. 4).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A similar scenario may be applicable to the CD94/NKG2A expressed on donor T cells during aGVHD, which may represent an intrinsic mechanism that limits aGVHD pathology. Consistent with this notion, donor T cells expanded progressively in the spleen and liver during days 7-14 after transfer, but this expansion was rather suppressed during days [14][15][16][17][18][19][20][21] in the present aGVHD model (Fig. 4).…”
Section: Discussionsupporting
confidence: 82%
“…It has recently been reported that CD94/NKG2A can be also expressed by T cells and inhibit T cell activation in vitro [17][18][19][20][21][22]. Moreover, increased expression of CD94 on human peripheral blood CD8 + T cells has been noted after allogeneic BMT [23].…”
Section: Introductionmentioning
confidence: 99%
“…Results from murine studies largely corroborate with the data obtained from human-based experiments. CD94/NKG2A partially inhibits murine allospecific CTL cytotoxicity and inhibits polyoma virus-specific CTL lysis, but not IFN-␥ production (55,56,62). However, CD94/NKG2A does not inhibit OVA peptide (SIINFEKL)-specific or lymphocytic choriomeningitis virus-specific CTL effector function (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…granzyme B, AGAGGACTAGAGCTGTGAGG; perforin, CACAGTAG AGTGTCCGATGTA; CD94, AACAATTGCACTGATGCCCAA; NKG2A/C, TCCTTCGGAAGGGCAGAGGTCA; NKG2E, CAAACTTATGCTCTT TGTCCA; NKG2D, GAGTCCTTGCTATAGCCTTG; ␤-actin, CAAGT GCTTCTAGGCGGACTGT. Probes for Ly49B and Ly49I were previously described (15,30,31). The oligonucleotides were 32 P-labeled using terminal transferase and hybridized at 58°C to Southern blots.…”
Section: Rt-pcr Analysis Of Nk Cell-associated Genesmentioning
confidence: 99%